4y = 12 - 5x
y = (12 - 5x) / 4
y = (- 5/4) x + 3
2007-07-17 20:21:57
·
answer #1
·
answered by Como 7
·
1⤊
0⤋
Y=0
2007-07-17 16:01:12
·
answer #2
·
answered by The Last Redneck Soxfan 2
·
0⤊
0⤋
Algebra.. my favorite subject. In order to solve for y, you have to make x=0. So when you replace x with 0, it would look like
5(0)+4y=12..
After you do that, 5 x 0 = 0 so what you have left is 4y=12
From there it's easy. You divide both sides by 4. 4y/4 and 12/4. Y is then left alone and it is equal to 3.
Y=3
2007-07-17 15:29:58
·
answer #3
·
answered by misa 1
·
0⤊
1⤋
y=3
2007-07-17 16:06:42
·
answer #4
·
answered by siddartha t 2
·
0⤊
0⤋
5x + 4y = 12
4y = 12 -5x
y = 1/4(12 - 5x) = 3 - 5x/4
2007-07-17 15:26:43
·
answer #5
·
answered by Bazz 4
·
0⤊
0⤋
Hey there!
Here's the answer.
5x+4y=12 --> Write the problem.
4y=12-5x --> Subtract 5x on both sides of the equation.
y=3-5/4x --> Divide 4 on both sides of the equation.
y=-5/4x+3 Use symmetric property of equality i.e. if a=b, then b=a.
So the answer is y=-5/4x+3 or y=-1.25x+3.
Hope it helps!
2007-07-17 15:27:47
·
answer #6
·
answered by ? 6
·
0⤊
0⤋
5x + 4y = 12
4y = 12 - 5x
y = (12 - 5x) / 4
2007-07-17 15:35:19
·
answer #7
·
answered by ferdie 2
·
0⤊
0⤋
4y=12-5x
y=(12-5x)/4
thankz for the points
2007-07-17 15:29:26
·
answer #8
·
answered by kate 2
·
0⤊
0⤋
y= -5/4x+3
5x+4y=12
-5x -5x
4y=12-5x
Divide by 4 on each side
4y/4=12/4-5/4x
y=3-5/4x
2007-07-17 15:24:01
·
answer #9
·
answered by Connie 2
·
0⤊
0⤋
y= -(5/4)*x+3
2007-07-17 15:25:17
·
answer #10
·
answered by ? 5
·
0⤊
0⤋